Wearable kinematic and physiological biofeedback system for movement-based relaxation. - Kumar D; Foody J; Markham C; Ward T; Caulfield B (Physiotherapy Ireland, 2005)
The primary aim of this project is to develop an effective feedback system for a human interface with a video game designed to promote mental and physical relaxation. Therapies such as Tai Chi and Yoga have been shown to have many therapeutic benefits in rehabilitation including enhancing postural awareness and reducing chronic pain and hypertension. We aim to develop a computer game in which the player's performance is determined by their ability to master one of these physical arts and in doing so bring about a state of mental relaxation. A garment based physiological and kinematic measurement system will provide our primary method of communication with the video game. This lightweight garment will monitor heart and breathing rate, muscle activity, galvanic skin response and alignment of body segments using embedded miniature sensors.The player must reproduce physical postures displayed by a model on screen whilst maintaining a relaxed and controlled breathing pattern. Feedback is provided by means of reproduction of the player's body image on screen. Quality of movement and posture, and degree of mental relaxation will determine the player's performance. This system could be used by patients suffering from many conditions including hypertension, anxiety disorder and chronic pain. We hope that this work will eventually lead to development of wearable feedback training systems for other exercise therapies such as core stability training.